Intraoral low-temperature degradation of monolithic zirconia dental prostheses: Results of a prospective clinical study with ex vivo monitoring. Issue 7 (July 2021) - Koenig, V.; Bekaert, S.; Dupont, N.; Vanheusden, A.; Le Goff, S.; Douillard, T.; Chevalier, J.; Djaker, N.; Lamy de la Chapelle, M.; Amiard, F.; Dardenne, N.; Wulfman, C.; et al.
Highlights: LTD develops in full zirconia prostheses after 6 months and increases with time. Glaze does not protect from LTD. LTD process is different in occlusal areas, where grain-pull out was observed. m phase quantification induces LTD underestimation in areas submitted to stress. LTD clinical impact is unknown and needs to be further studied. Abstract: Objective: To investigate the intraoral development and kinetics of low-temperature degradation (LTD) in second-generation 3 mol.% yttria-doped tetragonal zirconia polycrystal (3Y-TZP) monolithic prostheses, as well as the influence of masticatory mechanical stress and glaze layer on it. Methods: A total of 101 posterior tooth elements were included in a prospective clinical study, which included ex vivo LTD monitoring (at baseline, 6 months, 1 year, and 2 years) using Raman spectroscopy (n = 2640 monoclinic phase measurement points per evaluation time) and SEM. Four types of areas (1–2 mm 2 surface, 6 on molars, and 4 on premolars) were analyzed on each element surface: occlusal, axial, glazed, or unglazed. Raman depth mapping and high-resolution SEM were performed on the selected samples. Results: LTD developed in 3Y-TZP monolithic restorations 6 months after intraoral placement and progressed with time. After two years, the tetragonal-to-monoclinic transformation was non-uniform, with the presence of localized clusters of transformed grains. In axial areas, the grain aspect was typical of the classical nucleation-growth process reported for LTD, which progresses from the surface to a depth of several tens of microns. However, in occlusal areas, tribological stress generated surface crushing and grain pull-out from the clusters, which induced an underestimation of the aging process when the evaluation was limited to monoclinic phase quantification. Glazing cannot be considered a protection against LTD. Significance: If LTD occurs in dental prostheses in the same way as in orthopedic prostheses, its clinical impact is unknown and needs to be further studied.